Interventions for treatment and/or prevention of alcohol hangover: Systematic review - Jayawardena, Ranil; Thejani, Thulasika; Ranasinghe, Priyanga; Fernando, Dinithi; Verster, Joris C. (Human psychopharmacology, 2017)
Objective To evaluate new research conducted over the past few years (2009–2016) assessing the effectiveness of potentially curative and/or preventive methods of alcohol hangover. Methods Data were retrieved by a 4‐stage systematic search process. A search of the online Pubmed and Scopus databases were performed, using a combination of keywords: “Alcohol,” “Ethanol,” and “C2H5OH,” in combination with the terms “Hangover,” “Treatment,” and “Prevention.” The search comprised studies listed between January 1, 2009 and June 30, 2016. Findings were synthesized using a systematic approach. Quantitative analysis was not done because of the heterogeneity of the included studies. Results Six controlled human studies were identified (placebo controlled—3, controlled studies with a comparator intervention—3). Of the interventions, the use of polysaccharide rich extract of Acanthopanax senticosus, red ginseng antihangover drink, Korean pear juice, KSS formula, and the After‐Effect© were associated with a significant improvement of hangover symptoms (p < .05). The highest improvement was observed for the following symptoms: tiredness, nausea/vomiting, and stomachache. None of the methods were effective for all the symptoms. Conclusion The available evidence suggests that several products are capable of significantly improving some, but not all, of the symptoms related to alcohol hangover. Therefore, further research is necessary to develop clinically effective hangover treatments.